A biomarker based on gene expression indicates plant water status in controlled and natural environments. (29th May 2013) - MARCHAND, GWENAËLLE; MAYJONADE, BAPTISTE; VARÈS, DIDIER; BLANCHET, NICOLAS; BONIFACE, MARIE‐CLAUDE; MAURY, PIERRE; NAMBININA, FETY ANDRIANASOLO; BURGER, PHILIPPE; DEBAEKE, PHILIPPE; CASADEBAIG, PIERRE; VINCOURT, PATRICK; LANGLADE, NICOLAS B.
Abstract: Plant or soil water status is required in many scientific fields to understand plant responses to drought. Because the transcriptomic response to abiotic conditions, such as water deficit, reflects plant water status, genomic tools could be used to develop a new type of molecular biomarker. Using the sunflower ( Helianthus annuus L. ) as a model species to study the transcriptomic response to water deficit both in greenhouse and field conditions, we specifically identified three genes that showed an expression pattern highly correlated to plant water status as estimated by the pre‐dawn leaf water potential, fraction of transpirable soil water, soil water content or fraction of total soil water in controlled conditions. We developed a generalized linear model to estimate these classical water status indicators from the expression levels of the three selected genes under controlled conditions. This estimation was independent of the four tested genotypes and the stage (pre‐ or post‐flowering) of the plant. We further validated this gene expression biomarker under field conditions for four genotypes in three different trials, over a large range of water status, and we were able to correct their expression values for a large diurnal sampling period. Abstract : The need for a precise and robust environmental description is required in many scientific fields to explain how organisms respond to their abiotic and biotic environments. Using the sunflower crop as a model, we developed a novel type of biomarker based on gene expression and able to estimate the water available to the plant in controlled and natural conditions. This new kind of molecular tool will be of great interest for eco‐physiology, molecular physiology and genetics.